Another Pre-1592 Copy of the English Faust Book - Fehrenbach, R J (Library, 2019)
Abstract A second copy of a pre-1592 edition of the English Faust Book, Marlowe’s source for Doctor Faustus, has been uncovered in a catalogue of books owned by a London apothecary. This catalogue, of which at least a quarter are books associated with an apothecary’s profession, was compiled by the owner himself, one Edward Barlow, and, most importantly, is firmly dated 17 November 1589/90. This discovery, made by Peter Murray Jones of King’s College, Cambridge, is the second appearance of that book prior to the publication of its only extant edition in 1592, providing confirmation that Marlowe could have written Faustus prior to 1592. But whenever Marlowe wrote his play, the medico-magical material he employed had its source in a work that a practising apothecary judged valuable enough to add to his other professional books. The complete record of Jones’s discovery is found in Volume IX of Private Libraries in Renaissance England, PLRE 263.157.